The NH2-terminal arms of trp repressor participate in repressor/operator association. - Hurlburt, B K (1992)
The 3-dimensional structure of the trp repressor, aporepressor, and repressor/operator complex have been described. The NH2-terminal arms of the protein, comprising approximately 12-14 residues, were not well resolved in any of these structures. Previous studies by Carey showed that the arms are required for full in vitro repressor activity. To examine the roles of the arms more fully we have removed codons 2-5 and 2-8 of the trpR gene and analyzed the resulting truncated repressors in vivo and in vitro. The delta 2-5 trp repressor was found to be approximately 25% as active as the wild type repressor in vivo. In in vitro equilibrium binding experiments, the delta 2-5 trp repressor was shown to be five-fold less active in operator binding. The rate of dissociation of the complex formed between the delta 2-5 trp repressor and operator was essentially the same as the rate of dissociation of the wild type trp repressor/operator complex. However association of the delta 2-5 trp repressor with operator was clearly defective. Since the NH2-terminal arms of the trp repressor appear to affect association predominantly they may play a role in facilitating non-specific association of repressor with DNA as repressor seeks its cognate operators. The delta 2-8 trp repressor was unstable in vivo and in vitro, suggesting that some portion of the NH2-terminal arm is required for proper folding of the remainder of the molecule.